History wars and the classroom : global perspectives - Taylor, Tony; Guyver, Robert (Studies in the history of education (Greenwich, Conn.), 2012)
The book is entitled History Wars in the Classroom: Global Perspectives and examines how ten separate countries have experienced debates and disputes over the contested nature of the subject, for example the 'Black Armband' and 'Whitewash' factions in Australia who adopt opposingly celebratory or denigratory views of Australian history, especially when evaluating episodes of poor racial relations. There are also tensions between traditional/patriotic views of history teaching and reformed or 'new' history. There are issues of political control of the curriculum and parallel issues of who writes it (very topical in England at the moment over two expat 'big picture' historians who work at Harvard and Columbia (Niall Ferguson and Simon Schama)).